A Prospective Cohort Study of the Clinical Predictors of Bacteremia in Under-Five Children With Acute Undifferentiated Fever Attending a Secondary Health Facility in Northwestern Nigeria - Ogunkunle, Taofik Oluwaseun; Adedoyin, Timothy Olanrewaju; Ernest, Samuel Kolade; Hassan-Hanga, Fatimah; Imam, Abdulazeez; Olaosebikan, Rasaq; Obaro, Stephen K. (Frontiers in Pediatrics, 2022)
Background: Children with acute febrile illness with no localizing signs often receive antibiotics empirically in most resource-poor settings. Little is however known about the burden of bacteraemia in this category of patients and an appraisal is thus warranted. This will guide clinical practice and promote rational antibiotics use. Methods: We prospectively followed up 140 under-five children who presented with acute undifferentiated fever at the emergency/out-patient paediatric unit of a secondary healthcare facility. Baseline clinical and laboratory information was obtained and documented in a structured questionnaire. We compared baseline characteristics between participants with bacteraemia and those without bacteraemia. We further fitted a multivariable logistic regression model to identify factors predictive of bacteraemia among the cohort. Result: The prevalence of bacteraemia was 17.1% and Salmonella typhi was the most frequently (40.9%) isolated pathogen. The majority (78.6%) of the study participants were managed as out-patients. The participants who required admission were thrice likely to have bacteraemia when compared to those managed as out-patients (AOR -3.66 95% CI -1.11 to 12.08). There is a 14% increase in the Bacteraemia odds (AOR 1.14, 95% CI -1.02 to 1.27) with a daily increase in the duration of fever. Similarly, participants who were admitted with lethargy were 6.5 times more likely to have bacteraemia (AOR - 6.46, 95% CI -1.27 to 32.80). Other significant predictors were tachypnoea and lymphopenia. Conclusion: Among under-five children with acute undifferentiated fever. Longer duration of fever, lethargy, in-patient care, tachypnea and lymphopenia were the significant predictors of bacteraemia